Pengaruh Financial Technology dan Financial Literacy terhadap Sustainability UMKM di Kabupaten Karawang - Mohamad Iksan Abidin; Yanti; Lilis Lasmini (Syntax Corporation, 2023)
The purpose of this research is to examine the influence of Financial Technology (fintech) and Financial Literacy on the sustainability of micro, small, and medium-sized enterprises (MSMEs) in Karawang Regency. The population in this study consists of all registered MSMEs in Karawang Regency. The researcher used a saturation sampling method, where the entire population was included as the sample. The primary data collection method used in this study was through a questionnaire survey. The data analysis technique employed in this research was multiple regression analysis using SmartPLS 4.0 as the testing tool. The research results indicate that there is no significant influence of fintech on business sustainability. However, for the variable of Financial Literacy, there is a positive influence of Financial Literacy on the sustainability of MSMEs. This finding suggests to the government as the regulator, academia as the educator, private sector as the catalyst, and the community as the promoter to socialize and develop fintech and financial literacy among MSMEs in Karawang Regency in particular.